2015
DOI: 10.1016/j.cell.2015.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Regulation of Sensory Perception by a Female Hormone Alters Behavior

Abstract: SUMMARY Females may display dramatically different behavior depending on their state of ovulation. This is thought to occur through sex-specific hormones acting on behavioral centers in the brain. Whether incoming sensory activity also differs across the ovulation cycle to alter behavior has not been investigated. Here, we show that female mouse vomeronasal sensory neurons (VSNs) are temporarily and specifically rendered “blind” to a subset of male-emitted pheromone ligands during diestrus yet fully detect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 37 publications
8
167
0
Order By: Relevance
“…One possible mechanism is to alter sensory inputs to the MeA, at the levels of the VNO and AOB. Indeed, a number of studies have shown that responses of VNO sensory neurons can be modulated by hormones, internal status, and sensory experience in a sex-specific manner (Dey et al, 2015; Halem et al, 2001; Tachikawa et al, 2013; Xu et al, 2016). At the level of the accessory olfactory bulb, mating causes a lasting increase in baseline activity by selective regulation of local inhibition (Binns and Brennan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is to alter sensory inputs to the MeA, at the levels of the VNO and AOB. Indeed, a number of studies have shown that responses of VNO sensory neurons can be modulated by hormones, internal status, and sensory experience in a sex-specific manner (Dey et al, 2015; Halem et al, 2001; Tachikawa et al, 2013; Xu et al, 2016). At the level of the accessory olfactory bulb, mating causes a lasting increase in baseline activity by selective regulation of local inhibition (Binns and Brennan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mice are known to possess irregularities in their estrous cycle, as assessed by vaginal cytology, and are susceptible to interference by environmental and social factors, posing technical challenges not evident in the rat (33). Some of these potential factors affecting mouse reproductive cyclicity are transmitted through the olfactory system (34), a known substrate for progesterone action (35). Variability in the mouse estrous cycle is often addressed by experimental simulations of specific estrous cycle events, including pheromone-activated LH surges and hormone-activated LH surges in ovariectomized mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ovulating female mice release pheromones to attract males (Haga-Yamanaka et al, 2014), and juvenile females lacking mature gametes release a peptide pheromone to inhibit male courtship behavior (Ferrero et al, 2013). In addition, the ability of female mice to detect attractive male pheromones depends on the ovulation status signaled by a sex hormone (Dey et al, 2015). Similarly, in Drosophila melanogaster only sexually mature females produce 7,11-heptacosadiene (Arienti et al, 2010; Bilen et al, 2013), an aphrodisiac pheromone that promotes male courtship (Antony et al, 1985; Billeter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%